APPLICATION OF α-GLYCERYLPHOSPHORYLCHOLINE IN THE COMPREHENSIVE TREATMENT SCHEME FOR FUNCTIONAL RECOVERY AFTER CEREBRAL HEMISPHERIC ISCHEMIC STROKE - O.O. Pushko; N.V. Lytvynenko (Проблеми екології та медицини)
The article considers the influence of α-glycerylphosphorylcholine in the scheme of comprehensive therapy on the dynamics of functional recovery in patients with cerebral hemispheric ischemic stroke. Against the background of the progressive growth of acute cerebral infarction, the problem of timely care is relevant. Timely treatment of stroke, based on evidence-based medicine, along with early activation and rehabilitation of patients is designed to reduce mortality and subsequent disability of patients. Given that cholinergic insufficiency and structural and functional damage of neurons play an important role in the pathogenesis of post-stroke disorders, the use of medicines for their correction, in particular α-glycerylphosphorylcholine, is justified. Choline alfoscerate, a precursor of acetylcholine and phosphatidylcholine, is broken down by enzymes into choline and glycerophosphate when ingested, and the choline thus obtained is able to improve neuronal functionality in patients with neurodegenerative and vascular diseases. The study revealed a significantly better recovery of impaired motor and cognitive functions after cerebral hemispheric stroke under the influence of comprehensive therapeutic and rehabilitation measures using active rehabilitation methods in conjunction with α-glycerylphosphorylcholine. The results obtained during the study allow us to report the advantage of a combination of methods of active rehabilitation and the use of the pharmacological agent α-glycerylphosphorylcholine. The feasibility and efficacy of α-glycerylphosphorylcholine are related to its ability to reduce motor and cognitive deficits after ischemic stroke. The scheme of comprehensive treatment of patients in acute and restorative periods of cerebral hemispheric ischemic stroke with the use of α-glycerylphosphorylcholine helps to increase the effectiveness of functional recovery after an acute cerebral accident, and can be used in the use of therapeutic and rehabilitation programs for patients after cerebral hemispheric ischemic stroke to reduce the post-stroke deficit.